A process model for creating a brand in Japanese small business - Inagaki, Yuhsuke; katsura, Shintaro (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
This paper examines the process through which small firms with few management resources build their brands. We have considered small firms in the manufacturing industry for this case study. Building an in-house brand involves management strategy, business planning, and management evaluation in Phase 1; product development in Phase 2; customer development and distribution in Phase 3; and human resource development in Phase 4. Through this study, we have presented a specific framework for brand building and corporate growth.